Pengaruh Reputasi KAP, Opini Auditor, Kompleksitas Perusahaan terhadap Audit Delay: Studi Empiris Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2015-2019 - Zahra Mawar Dhani; Kenny Ardillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Audit delay is a company that reports financial reports late. Auditor change is the change of KAP and auditor by the company. This study aims to analyze the reputation of KAP, auditor opinion, company complexity, and management changes, on audit delay in manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The reputation of KAP uses dummy variables, auditors' opinion is measured using dummy variables, company complexity is measured by dummy variables, and management changes are measured by dummy variables. The auditor turnover is measured by a dummy variable. The population in this study were 193 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019.